MANAJEMEN STRATEGI PARIWISATA DALAM KETAHANAN PEREKONOMIAN PADA MASA PANDEMI COVID-19 OLEH DINAS PARIWISATA, KEPEMUDAAN, DAN OLAHRAGA KABUPATEN MOJOKERTO (STUDI PADA UBALAN WATERPARK) - Novrima Wahyu Danarsasi; Meirinawati Meirinawati (Publika, 2022)
Tourism is a significant economic sector in Indonesia. Mojokerto Regency, East Java, is one place with good tourism potential that deserves to be utilised as a tourist destination. COVID-19's existence has impacted tourism development and economic progress in the tourism sector. Based on the existing issues, the Mojokerto Regency Department of Tourism, Youth, and Sports is attempting to develop a strategy to address the impact of the Covid-19 epidemic on the tourism sector. The goal of this study is to look at the Department of Tourism, Youth, and Sports of Mojokerto Regency's strategic management of the tourism sector in the context of economic resilience during the pandemic. The theory in Fred.book, R.David's (2011) on Strategic Management, especially strategy formulation, strategy implementation, and strategy evaluation, is the topic of the research. The research approach used in this study is descriptive qualitative research. Interviews, documentation, and observation are all used to acquire data. Data collection, data reduction, data display, and conclusion drawing/verification were all done in real time during qualitative data analysis. The research findings on the topic of strategy formation are generally positive, albeit there are some flaws. Managers are provided training and coaching to help them improve their skills as part of the implementation. During the pandemic, when tourism objects were opened, Disparpora and Ubalan's strategies included the implementation and supervision of strict health protocols, tourism promotion, and the use of IT and media, which were already quite good; the only problem was that Ubalan's social media had little content. The adoption of the strategy can gradually enhance tourist visits during the assessment stage, albeit this has not been maximized because the quota for tourist attraction visitors is still limited. Building Ubalan social media material, socializing the "Tourism Information Center," doing routine training and implementing reward and punishment, and developing online marketing techniques are among the proposals made. Keywords: Strategic Management, Tourism, Disparpora